Graphene-copper composite materials and their preparation methods

CN122942007APending Publication Date: 2026-10-20浙江泰镒新材料科技有限公司 +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611437333.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-16
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]然而,现有的石墨烯铜复合材料的抗氧化性能较差,有待进一步提高

Benefits of technology

[0019]本申请实施例提供的石墨烯铜复合材料,其中,石墨烯薄膜中的单晶石墨烯尺寸L与石墨烯铜复合材料的表面粗糙度RMS的比值L/RMS满足:444≤L/RMS≤11000,可以看出,L/RMS的数值越大,说明单晶石墨烯尺寸L越大,石墨烯铜复合材料的表面粗糙度RMS越低。现有工艺制得的石墨烯铜复合材料中,石墨烯薄膜中的单晶石墨烯尺寸L通常为2μm~9μm,石墨烯铜复合材料的表面粗糙度RMS通常为40nm~100nm,L/RMS的数值范围为20~225,通过对比可以看出,本申请实施例制备的石墨烯铜复合材料的L/RMS远远大于现有工艺制备的石墨烯铜复合材料的L/RMS,说明本申请实施例提供的石墨烯铜复合材料中,石墨烯薄膜具有较大的单晶石墨烯尺寸,从而可以减少石墨烯薄膜中的晶界数量,提升石墨烯薄膜的电学性能,并且,石墨烯铜复合材料整体的表面粗糙度RMS较低,表面较为平滑,说明石墨烯薄膜以平铺的方式设置于铜基体上,二者贴合紧密,有效减少了石墨烯薄膜与铜基体之间的界面间隙,从而可以避免铜基体被氧化,提升石墨烯铜复合材料的抗氧化性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This application provides a graphene-copper composite material and its preparation method. The graphene-copper composite material includes a copper matrix and a graphene film attached to the surface of the copper matrix. The ratio of the size L of the single-crystal graphene in the graphene film to the surface roughness RMS of the graphene-copper composite material, L / RMS, satisfies: 444 ≤ L / RMS ≤ 11000. The graphene-copper composite material provided in this application has a large single-crystal graphene size, which reduces the number of grain boundaries in the graphene film and improves its electrical properties. Furthermore, the overall surface roughness RMS of the graphene-copper composite material is low, and the surface is relatively smooth, indicating that the graphene film is laid flat on the copper matrix, and the two are tightly bonded, effectively reducing the interfacial gap between the graphene film and the copper matrix. This prevents the copper matrix from being oxidized and improves the oxidation resistance of the graphene-copper composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of carbon nanomaterials technology, and in particular to a graphene-copper composite material and its preparation method. Background Technology

[0002] Graphene has very high specific surface area, electron mobility, Young's modulus and thermal conductivity, and has broad application prospects in many fields such as lithium-ion batteries, transparent conductive films, supercapacitors, fuel cells, solar cells and hydrogen storage materials.

[0003] Copper is widely used in power, transportation, industrial equipment and electronic information fields due to its good electrical conductivity, thermal conductivity and ductility.

[0004] In existing technologies, graphene is usually combined with metallic copper, for example, by vapor deposition of a graphene layer on the surface of a copper substrate, in order to obtain a graphene-copper composite material that combines the excellent properties of both metallic copper and graphene.

[0005] However, the existing graphene-copper composite materials have poor oxidation resistance and need further improvement. Summary of the Invention

[0006] Based on this, embodiments of this application provide a graphene-copper composite material and a method for preparing the same, in order to at least partially solve the above-mentioned technical problems.

[0007] In a first aspect, embodiments of this application provide a graphene-copper composite material, comprising a copper matrix and a graphene film attached to the surface of the copper matrix, wherein the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 444≤L / RMS≤11000.

[0008] In some embodiments, the macroscopic physical morphology of the copper substrate is selected from at least one of copper foil, copper plate, copper strip, copper block, copper powder, copper foam, and copper wire; The average thickness of the copper foil is 20μm~100μm; The average thickness of the copper plate is 100μm~1000μm; The equivalent circle diameter of the cross-section of the copper strip is 5mm to 15mm; The volume of the copper block is 1 cm³. 3 ~100cm 3 ; The average particle size of the copper powder is 15μm~50μm; The specific surface area of ​​the copper foam is 0.2 m². 2 / g~0.8m 2 / g; The equivalent circle diameter of the cross-section of the copper wire is 0.05mm to 5mm.

[0009] In some embodiments, the macroscopic physical morphology of the copper substrate is selected from at least one of copper foil, copper plate, copper strip, and copper block; the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 800≤L / RMS≤11000. The single-crystal graphene size L in the graphene film satisfies: 24μm≤L≤55μm; the surface roughness RMS of the graphene-copper composite material satisfies: 5nm≤RMS≤30nm.

[0010] In some embodiments, the monolayer ratio of the graphene film is 90%~98%; and / or, The graphene film has a 2D / G strength ratio of 1.9 to 4.6; and / or, The graphene film has a D / G intensity ratio of 0.03 to 0.09.

[0011] In some embodiments, the macroscopic physical morphology of the copper substrate is selected from at least one of copper powder, copper foam, and copper wire; the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 444≤L / RMS≤2000. The single-crystal graphene size L in the graphene film satisfies: 20μm≤L≤32μm; the surface roughness RMS of the graphene-copper composite material satisfies: 16nm≤RMS≤45nm.

[0012] In some embodiments, the monolayer ratio of the graphene film is 82% to 92%; and / or, The graphene film has a 2D / G intensity ratio of 1.7 to 3.4; and / or, The graphene film has a D / G intensity ratio of 0.05 to 0.13.

[0013] Secondly, embodiments of this application provide a method for preparing a graphene-copper composite material, comprising: Provide a copper substrate and remove the natural oxide layer on the surface of the copper substrate; The copper substrate is subjected to oxygen plasma treatment to generate an artificial oxide layer on the surface of the copper substrate; The copper substrate is annealed in a hydrogen atmosphere to remove the artificial oxide layer; A graphene film is grown on the surface of the copper substrate to obtain a graphene-copper composite material.

[0014] In some embodiments, removing the natural oxide layer on the surface of the copper substrate includes immersing the copper substrate in a hydrochloric acid solution for 30 to 120 seconds, wherein the mass percentage of hydrochloric acid in the hydrochloric acid solution is 0.86 wt% to 4.31 wt%.

[0015] In some embodiments, the oxygen plasma treatment of the copper substrate includes: The copper substrate is placed in the reaction chamber of the plasma processing equipment, and oxygen is introduced into the reaction chamber at a flow rate of 3 sccm to 50 sccm. The radio frequency power supply of the plasma processing equipment is turned on, with an output power of 150W to 400W and a processing time of 150 seconds to 400 seconds.

[0016] In some embodiments, the annealing treatment of the copper substrate in a hydrogen atmosphere includes: In a vacuum environment, or with an inert gas introduced, the copper substrate is heated to 1000°C to 1060°C. Hydrogen gas is introduced to form a hydrogen atmosphere, and the copper substrate is kept at 1000℃~1060℃ for 20 minutes to 40 minutes in the hydrogen atmosphere.

[0017] In some embodiments, the flow rate of the hydrogen gas is 100 sccm to 400 sccm.

[0018] In some embodiments, after an artificial oxide layer is formed on the surface of the copper substrate, the oxygen content of the copper substrate having the artificial oxide layer is 60ppm to 650ppm; and / or, the Cu / O atomic ratio of the artificial oxide layer is 1 to 4.

[0019] The graphene-copper composite material provided in this application embodiment has a ratio L / RMS of the size L of the single-crystal graphene in the graphene film to the surface roughness RMS of the graphene-copper composite material, which satisfies the following condition: 444≤L / RMS≤11000. It can be seen that the larger the value of L / RMS, the larger the size L of the single-crystal graphene and the lower the surface roughness RMS of the graphene-copper composite material. In existing graphene-copper composite materials, the size L of single-crystal graphene in the graphene film is typically 2μm~9μm, the surface roughness RMS of the graphene-copper composite material is typically 40nm~100nm, and the L / RMS value ranges from 20 to 225. A comparison shows that the L / RMS of the graphene-copper composite material prepared in this application is significantly larger than that of graphene-copper composite materials prepared by existing processes. This indicates that the graphene film in the graphene-copper composite material provided in this application has a larger single-crystal graphene size, which can reduce the number of grain boundaries in the graphene film and improve its electrical properties. Furthermore, the overall surface roughness RMS of the graphene-copper composite material is low, and the surface is relatively smooth, indicating that the graphene film is laid flat on the copper substrate, and the two are tightly bonded, effectively reducing the interfacial gap between the graphene film and the copper substrate. This prevents the copper substrate from being oxidized and improves the oxidation resistance of the graphene-copper composite material. Attached Figure Description

[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below.

[0021] Figure 1 A flowchart illustrating the preparation method of the graphene-copper composite material provided in this application embodiment. Detailed Implementation

[0022] The technical solutions in the embodiments of this application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.

[0023] In this application, "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural.

[0024] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one," "at least one of the following," or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c," or "at least one of a, b, and c," can both mean: a, b, c, a+b, a+c, b+c, or a+b+c, where a, b, and c can be single or multiple.

[0025] Various embodiments of this application may exist in the form of a range; it should be understood that the description in the form of a range is merely for convenience and brevity and should not be construed as a hard limitation on the scope of this application; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within that range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., and single numbers within the range, such as 1, 2, 3, 4, 5, and 6. Furthermore, whenever a numerical range is referred to herein, it means including any referenced number (fraction or integer) within the range referred to.

[0026] This application provides a graphene-copper composite material, comprising a copper matrix and a graphene film attached to the surface of the copper matrix. The ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 444≤L / RMS≤11000. For example, L / RMS can be 444, 480, 533, 650, 720, 857, 1000, 1500, 2000, 3000, 4000, 5000, 6000, 7000, 8000, 9000, 10000, 11000, etc.

[0027] The graphene-copper composite material provided in this application embodiment has a ratio L / RMS of the size L of the single-crystal graphene in the graphene film to the surface roughness RMS of the graphene-copper composite material, which satisfies the following condition: 444≤L / RMS≤11000. It can be seen that the larger the value of L / RMS, the larger the size L of the single-crystal graphene and the lower the surface roughness RMS of the graphene-copper composite material. In existing graphene-copper composite materials, the size L of single-crystal graphene in the graphene film is typically 2μm~9μm, the surface roughness RMS of the graphene-copper composite material is typically 40nm~100nm, and the L / RMS value ranges from 20 to 225. A comparison shows that the L / RMS of the graphene-copper composite material prepared in this application is significantly larger than that of graphene-copper composite materials prepared by existing processes. This indicates that the graphene film in the graphene-copper composite material provided in this application has a larger single-crystal graphene size, which can reduce the number of grain boundaries in the graphene film and improve its electrical properties. Furthermore, the overall surface roughness RMS of the graphene-copper composite material is low, and the surface is relatively smooth, indicating that the graphene film is laid flat on the copper substrate, and the two are tightly bonded, effectively reducing the interfacial gap between the graphene film and the copper substrate. This prevents the copper substrate from being oxidized and improves the oxidation resistance of the graphene-copper composite material.

[0028] It should be noted that the macroscopic physical form of the copper substrate is selected from at least one of copper foil, copper powder, copper foam, copper wire, copper strip, and copper block.

[0029] For example, the average thickness of the copper foil is 20μm to 100μm, such as 20μm, 40μm, 60μm, 80μm, 100μm, etc.

[0030] For example, the average thickness of the copper plate is 100μm to 1000μm, such as 100μm, 200μm, 400μm, 600μm, 800μm, 1000μm, etc.

[0031] For example, the equivalent circle diameter of the cross-section of the copper strip is 5mm to 15mm, such as 5mm, 7mm, 9mm, 10mm, 12mm, 14mm, 15mm, etc.

[0032] For example, the volume of the copper block is 1 cm³. 3 ~100cm 3 For example, 1cm 3 10cm 3 25cm 3 50cm 3 75cm 3 100cm 3 wait.

[0033] For example, the average particle size of the copper powder is 15μm to 50μm, such as 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, 45μm, 50μm, etc.

[0034] For example, the specific surface area of ​​the copper foam is 0.2 m². 2 / g ~0.8m 2 / g, for example 0.2m 2 / g, 0.3m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g etc.

[0035] For example, the equivalent circle diameter of the cross-section of the copper wire is 0.05mm to 5mm, such as 0.05mm, 0.1mm, 0.5mm, 1mm, 2mm, 3mm, 4mm, 5mm, etc.

[0036] For example, when the macroscopic physical morphology of the copper substrate is selected from at least one of copper foil, copper plate, copper strip, and copper block, the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 800≤L / RMS≤11000, for example, 800, 1000, 2000, 4000, 6000, 8000, 10000, 11000, etc.; wherein, the single-crystal graphene size L in the graphene film satisfies: 24μm≤L≤55μm, for example, 24μm, 30μm, 35μm, 40μm, 45μm, 50μm, 55μm, etc.; and the surface roughness RMS of the graphene-copper composite material satisfies: 5nm≤RMS≤30nm, for example, 5nm, 10nm, 15nm, 20nm, 25nm, 30nm, etc. The graphene film has a monolayer ratio of 90% to 98%, such as 90%, 92%, 94%, 96%, 98%, etc.; the graphene film has a 2D / G strength ratio of 1.9 to 4.6, such as 1.9, 2.5, 3.0, 3.5, 4.0, 4.6, etc.; the graphene film has a D / G strength ratio of 0.03 to 0.09, such as 0.03, 0.05, 0.07, 0.09, etc.

[0037] For example, when the macroscopic physical morphology of the copper substrate is selected from at least one of copper powder, copper foam, and copper wire, the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 444≤L / RMS≤2000, for example, 444, 500, 800, 1000, 1200, 1500, 1800, 2000, etc.; wherein, the single-crystal graphene size L in the graphene film satisfies: 20μm≤L≤32μm, for example, 20μm, 22μm, 24μm, 26μm, 28μm, 30μm, 32μm, etc.; and the surface roughness RMS of the graphene-copper composite material satisfies: 16nm≤RMS≤45nm, for example, 16nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, etc. The monolayer ratio of the graphene film is 82%~92%, for example, 82%, 84%, 86%, 88%, 90%, 92%, etc.; the 2D / G strength ratio of the graphene film is 1.7~3.4, for example, 1.7, 2.0, 2.4, 2.8, 3.2, 3.4, etc.; the D / G strength ratio of the graphene film is 0.05~0.13, for example, 0.05, 0.07, 0.09, 0.11, 0.13, etc.

[0038] It is understandable that a larger single-crystal graphene size can effectively reduce the number of grain boundaries within the graphene film, thereby reducing the scattering of electrons and phonons by the grain boundaries, and thus significantly improving the carrier mobility and thermal conductivity of the graphene-copper composite material. For example, the method for testing the single-crystal graphene size L includes: characterization using a scanning electron microscope (SEM), randomly selecting no fewer than 5 fields of view to directly observe the morphology of graphene domains on the copper substrate, measuring the longest diagonal or equivalent diagonal of each domain (for regular domains such as hexagons, directly measuring their longest diagonal; for irregular domains, measuring the longest diagonal of their equivalent area regular hexagon as the equivalent diagonal), and taking the maximum value of the domain size in all fields of view as the single-crystal graphene size L.

[0039] It is understood that the surface roughness RMS of the graphene-copper composite material refers to the overall roughness of the product obtained after depositing a graphene film on the copper substrate. A lower surface roughness RMS indicates a smoother surface, signifying a tighter adhesion between the graphene film and the copper substrate. This reduces the interfacial gap between the graphene film and the copper substrate, preventing oxidation of the copper substrate and improving the oxidation resistance of the graphene-copper composite material. For example, the test method for the surface roughness RMS of the graphene-copper composite material includes: characterization using atomic force microscopy (AFM) in tapping mode, with a scanning range of 1 μm × 1 μm, a scanning rate of 1.0 Hz, and a resolution of 512 × 512 pixels. The probe type is RTESP or a similar Si probe with an elastic constant of approximately 40 N / m and a resonant frequency of approximately 300 kHz.

[0040] Understandably, a high monolayer ratio indicates that the graphene film can maintain a highly uniform monolayer structure over a large area, thus ensuring that the graphene film has a consistent band structure and excellent electrical performance in electronic devices. For example, the method for testing the monolayer ratio of the graphene film includes: characterization using a 532nm wavelength Raman spectrometer, randomly selecting 100 test points within a 0.5cm × 0.5cm sample area, and collecting the Raman spectra at each point. The criteria for determining monolayer graphene are: the 2D peak exhibits a single Lorentz symmetric peak shape, and the intensity ratio of the 2D peak to the G peak (I0.05) is relatively high. 2D / I G ≥2. The single-layer rate is calculated according to the following formula: Single-layer rate = (Number of test points meeting the single-layer standard / Total number of test points) × 100%.

[0041] It is understandable that the 2D / G intensity ratio (i.e., I) 2D / I G This indicates a 2D peak (approximately 2700 cm⁻¹). -1 ) and G peak (approximately 1580cm) -1 The 2D / G intensity ratio is the ratio of the peak intensities of graphene crystals to the peak intensities of graphene crystals. The 2D / G intensity ratio is a key Raman indicator for evaluating the number of graphene layers. Generally, a higher 2D / G intensity ratio indicates fewer graphene layers and better monolayer properties. For example, the method for testing the 2D / G intensity ratio of the graphene film includes characterization using a 532 nm wavelength Raman spectrometer. 100 test points are randomly selected within a 0.5 cm × 0.5 cm sample area, each located within the graphene crystal domains, avoiding the domain edges. Raman spectra are collected at each point, and the 2D peak (approximately 2700 cm⁻¹) is read from each test point. -1 ) and G peak (approximately 1580cm) -1 The peak intensity of ) is calculated, and the peak intensity ratio (I) is calculated. 2D / I GThe average value of the results from 100 test points was taken as the 2D / G intensity ratio, and the standard deviation was calculated.

[0042] It is understandable that the D / G intensity ratio is a key Raman indicator characterizing the lattice defect density of graphene. Generally speaking, the lower the D / G intensity ratio, the fewer the lattice defects and the higher the crystal integrity of the graphene. For example, the method for testing the D / G intensity ratio of the graphene film includes: characterization using a 532 nm wavelength Raman spectrometer; randomly selecting 100 test points within a 0.5 cm × 0.5 cm sample area, with each test point located within the graphene domains, avoiding the domain edges; collecting the Raman spectra of each point; and reading the D peak (approximately 1350 cm⁻¹) of each test point. -1 ) and G peak (approximately 1580cm) -1 The peak intensity of ) is calculated, and the peak intensity ratio (I) is calculated. D / I G The average value of the results from 100 test points is taken as the D / G intensity ratio, and the standard deviation is calculated.

[0043] Please see Figure 1 This application also provides a method for preparing a graphene-copper composite material, used to prepare the graphene-copper composite material as described above, the preparation method comprising: S100, providing a copper substrate and removing the natural oxide layer on the surface of the copper substrate.

[0044] For example, the copper substrate is selected from at least one of copper foil, copper plate, copper strip, copper block, copper powder, copper foam, and copper wire. The dimensions of the copper substrate have been described in detail above and will not be repeated here.

[0045] It should be noted that the natural oxide layer formed on the copper substrate during storage and transportation is uneven in thickness and distributed in an island-like pattern. This non-uniform oxide layer undergoes asynchronous reduction during subsequent CVD heating and hydrogen annealing; that is, thinner areas of the oxide layer are preferentially reduced, while thicker areas are reduced later. This results in inconsistent etching levels across the copper surface, producing numerous pits, step bundles, and grain boundary trenches, which further deteriorates the surface roughness of the copper substrate. Therefore, removing the natural oxide layer from the copper substrate surface can eliminate the adverse effects of this non-uniform natural oxide layer on the subsequent reduction process, providing a clean and uniform starting surface for subsequent oxygen plasma treatment.

[0046] For example, removing the natural oxide layer on the surface of the copper substrate includes immersing the copper substrate in a hydrochloric acid solution for 30 to 120 seconds, such as 30 seconds, 45 seconds, 60 seconds, 90 seconds, 120 seconds, etc., wherein the mass percentage of hydrochloric acid in the hydrochloric acid solution is 0.86wt% to 4.31wt% (e.g., 0.86wt%, 1.0wt%, 1.5wt%, 2.0wt%, 2.5wt%, 3.0wt%, 3.5wt%, 4.0wt%, 4.31wt%, etc.).

[0047] For example, before immersing in hydrochloric acid solution, the copper substrate can be placed in acetone, anhydrous ethanol and deionized water in sequence and ultrasonically cleaned for 5 to 10 minutes (e.g. 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, etc.) to remove oil, organic contaminants and some particulate impurities from the surface of the copper foil.

[0048] For example, after soaking in hydrochloric acid solution, the copper substrate can be rinsed with a large amount of deionized water, then immersed in deionized water for ultrasonic rinsing for 3 to 8 minutes (e.g., 3 minutes, 5 minutes, 8 minutes, etc.), and finally thoroughly dried with a high-purity nitrogen gun.

[0049] S200, the copper substrate is subjected to oxygen plasma treatment to generate an artificial oxide layer on the surface of the copper substrate.

[0050] Understandably, by treating the copper substrate with oxygen plasma, the high activity and isotropy of oxygen plasma can be utilized to actively construct an artificial oxide layer with uniform and controllable thickness and chemical composition (Cu / O atomic ratio) on the copper substrate surface, overcoming the non-uniform characteristics of uneven thickness and island-like distribution in natural oxide layers. Due to its high uniformity in thickness and composition, the artificial oxide layer lays the structural foundation for simultaneous reduction and surface superplanarization reconstruction during subsequent hydrogen annealing.

[0051] For example, the oxygen plasma treatment of the copper substrate includes: placing the copper substrate in the reaction chamber of a plasma treatment device, introducing oxygen into the reaction chamber at a flow rate of 3 sccm to 50 sccm (e.g., 3 sccm, 5 sccm, 8 sccm, 10 sccm, 20 sccm, 30 sccm, 40 sccm, 50 sccm, etc.), turning on the radio frequency power supply of the plasma treatment device at an output power of 150W to 400W (e.g., 150W, 200W, 250W, 300W, 350W, 400W, etc.), and a treatment time of 150 seconds to 400 seconds (e.g., 150 seconds, 200 seconds, 250 seconds, 300 seconds, 350 seconds, 400 seconds, etc.). By synergistically controlling oxygen flow rate, radio frequency power, and processing time, a uniform and controllable artificial oxide layer (light brown or dark brown oxide film) with a specific thickness and chemical composition (Cu / O atomic ratio) can be generated on a clean copper surface. This provides a structural basis for simultaneous reduction and surface ultraplanarization during subsequent annealing. It is crucial to control the radio frequency output power within the range of 150W to 400W: too low a power (<150W) will result in an artificial oxide layer that is too thin or unevenly distributed, failing to effectively passivate the original defects on the copper substrate surface; too high a power (>400W) may cause plasma damage, making the artificial oxide layer too dense or etched, thus losing its controllability as a template for subsequent graphene growth. Optimizing the radio frequency output power range to 150W to 400W allows for atomic-level flatness and extremely low defect density on the annealed copper substrate surface. This helps reduce the graphene nucleation density, ultimately obtaining single-crystal graphene with larger dimensions, thereby significantly improving the carrier mobility and thermal conductivity of the graphene-copper composite material.

[0052] For example, after the copper substrate is subjected to oxygen plasma treatment to form an artificial oxide layer on its surface, the oxygen content of the copper substrate with the artificial oxide layer is 60ppm to 650ppm, such as 60ppm, 100ppm, 180ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, 550ppm, 600ppm, 650ppm, etc. By controlling the oxygen content within the range of 60ppm to 650ppm, it is ensured that the artificial oxide layer has a suitable total amount of oxygen, which not only ensures that the artificial oxide layer continuously and uniformly covers the copper surface, but also avoids the artificial oxide layer being too thick, which would lead to incomplete reduction or excessively long reduction time during subsequent hydrogen annealing. This provides a suitable oxygen source basis for the subsequent simultaneous reduction of the artificial oxide layer and the reconstruction of the surface ultraplanarization.

[0053] For example, the oxygen content test of the copper substrate with the artificial oxide layer includes: using an oxygen-nitrogen-hydrogen analyzer (ONH Analyzer) to test the oxygen content of the copper substrate by melting-infrared absorption method.

[0054] For example, after oxygen plasma treatment to generate an artificial oxide layer on the surface of the copper substrate, the Cu / O atomic ratio of the artificial oxide layer is 1 to 4, such as 1, 1.5, 2, 2.5, 3, 3.5, 4, etc. This application achieves optimal control of the active oxygen site concentration by controlling the Cu / O atomic ratio of the artificial oxide layer within the range of 1 to 4. When the oxygen content is too high, the excessive number of active oxygen sites on the copper substrate surface leads to excessive oxidation and consumption of carbon species, making effective nucleation and graphene growth difficult. When the oxygen content is too low, the insufficient number of active oxygen sites on the copper substrate surface fails to suppress spontaneous nucleation, resulting in increased graphene nucleation density and smaller single-crystal graphene size. Therefore, controlling the Cu / O atomic ratio of the artificial oxide layer to 1 to 4 ensures a suitable oxygen content on the copper substrate surface, laying the foundation for subsequent control of graphene nucleation density.

[0055] Exemplarily, the method for testing the Cu / O atomic ratio of the artificial oxide layer includes: using X-ray photoelectron spectroscopy (XPS) to test the Cu / O atomic ratio on the surface of the copper substrate (copper foil). High-resolution spectra of Cu 2p and O 1s are acquired, and the Cu 2p... 3 / 2 Peak fitting was performed on the O 1s peak, taking only the area of ​​the main peak (excluding satellite peaks); peak fitting was also performed on the O 1s peak, taking only the area of ​​the lattice oxygen peak (binding energy range of 529.0 eV~530.5 eV) to eliminate interference from surface adsorbed impurities. The atomic concentration ratio of Cu to O was calculated using the relative sensitivity factor method, thus obtaining the surface Cu / O atomic ratio.

[0056] S300, the copper substrate is annealed in a hydrogen atmosphere to remove the artificial oxide layer.

[0057] It should be noted that during hydrogen annealing, the artificial oxide layer on the copper substrate surface undergoes a reduction reaction with hydrogen at high temperature, resulting in a copper substrate with an ultra-flat surface. Because the thickness and chemical composition of this artificial oxide layer are highly uniform, the reduction reaction is triggered synchronously and at the same rate across the copper surface, avoiding the asynchronous reduction problem caused by the uneven thickness of the natural oxide layer. Simultaneously, the copper atoms released during reduction gain energy and undergo long-range migration and atomic-level rearrangement, directionally filling microscopic pits and defect sites to form a regular step-platform structure, resulting in a reconstructed copper substrate with an ultra-flat surface. This provides an ideal catalytic surface with extremely low nucleation density for subsequent graphene growth, fundamentally ensuring the growth conditions for large single-crystal graphene.

[0058] For example, the annealing treatment of the copper substrate in a hydrogen atmosphere includes: In a vacuum environment, the copper substrate is heated to 1000℃~1060℃ (e.g., 1000℃, 1010℃, 1020℃, 1030℃, 1040℃, 1050℃, 1060℃, etc.). Hydrogen gas is introduced to form a hydrogen atmosphere, and the copper substrate is kept at 1000℃~1060℃ for 20 minutes to 40 minutes (e.g., 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, etc.) in the hydrogen atmosphere.

[0059] By holding the copper substrate at 1000℃~1060℃ in a hydrogen atmosphere for 20 to 40 minutes, a reduction reaction occurs between the hydrogen and the uniform artificial oxide layer, achieving ultraplanar reconstruction of the copper substrate surface. This temperature window (1000℃~1060℃) ensures sufficient surface diffusion rate for copper atoms without causing excessive copper volatilization or abnormal grain growth due to excessive temperature. This time window (20 minutes to 40 minutes) provides sufficient kinetic conditions for the full migration of copper atoms and the formation of surface step-plateau structures, laying the foundation for the subsequent low nucleation density growth of graphene.

[0060] For example, the pressure of the vacuum environment can be below 200 Pa, such as 200 Pa, 180 Pa, 150 Pa, 120 Pa, 100 Pa, 80 Pa, 60 Pa, 50 Pa, etc.

[0061] For example, the flow rate of the hydrogen gas is 100 sccm to 400 sccm, such as 100 sccm, 200 sccm, 300 sccm, 400 sccm, etc. It should be noted that the reduction mechanism of hydrogen gas is as follows: hydrogen gas (H2) is adsorbed on the copper surface at high temperature and undergoes a reduction reaction with copper oxides (CuO and / or Cu2O): H2 + CuO → Cu + H2O, H2 + Cu2O → 2Cu + H2O; specifically, hydrogen molecules dissociate into active hydrogen atoms on the copper surface, and the hydrogen atoms combine with oxygen in the oxide lattice to form water. After the water molecules desorb from the copper surface, the remaining copper atoms constitute metallic copper.

[0062] It should be noted that although the artificial oxide layer is reduced during hydrogen annealing, it can still achieve subsequent regulation of graphene nucleation density through the following two irreversible effects: First, the active oxygen in the artificial oxide layer forms a suitable atomic-level step-platform structure on the copper surface through "oxygen etching" in the early stage of reduction. This morphology is retained after reduction, forcing carbon species to selectively nucleate along the step edges rather than randomly and explosively nucleating. Second, some of the active oxygen in the artificial oxide layer is locked into the copper lattice in the form of subsurface oxygen, slightly changing the surface work function and forming a "chemical potential trap" memory effect, guiding carbon species to stably attach at preset sites, thereby significantly reducing the nucleation density and promoting the growth of large single crystals.

[0063] S400, a graphene film is grown on the surface of the copper substrate to obtain a graphene-copper composite material.

[0064] Understandably, on a copper substrate with an ultra-flat surface, the nucleation density of graphene can be effectively suppressed, and individual crystal nuclei can obtain sufficient lateral growth space, ultimately resulting in large single-crystal graphene. At the same time, the copper-based self-limited growth mechanism can be used to achieve high monolayer ratio and low defect density.

[0065] For example, the growth of a graphene film on the copper substrate surface includes: maintaining the temperature of the copper substrate at 1000℃~1060℃, introducing a carbon source gas at a flow rate of 3sccm~30sccm (e.g., 3sccm, 5sccm, 8sccm, 10sccm, 15sccm, 20sccm, 25sccm, 30sccm, etc.), and a growth time of 5 minutes~30 minutes (e.g., 5 minutes, 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, etc.). For example, the carbon source gas includes at least one of methane, ethylene, and acetylene.

[0066] By controlling the carbon source gas flow rate within the low range of 3 sccm to 30 sccm, carbon atoms can be supplied to the copper surface at a gentle and continuous rate. This matches the extremely low nucleation density on the ultra-planarized copper substrate, providing ample raw material for the full lateral growth of individual crystal nuclei. Simultaneously, excessive flow rates prevent secondary nucleation or gas-phase side reactions, ensuring the orderly growth of single-crystal graphene. By controlling the growth time within the range of 5 to 30 minutes, favorable kinetic conditions are provided for the continuous supply of carbon atoms to the copper surface, surface diffusion, and ordered lattice arrangement. This ensures that single-crystal graphene grains reach a size of 20 μm to 55 μm under low nucleation density conditions, while avoiding the failure of the self-limiting mechanism and secondary nucleation due to overgrowth, achieving optimal control over the number of graphene layers and crystal quality.

[0067] For example, during graphene growth, hydrogen gas can be simultaneously introduced along with the carbon source gas (3 sccm~30 sccm). The hydrogen flow rate is 100 sccm~400 sccm. Hydrogen gas has a weak etching effect on weakly bonded carbon structures, which can preferentially remove amorphous carbon and the weak bond edges of multilayer graphene, effectively suppressing secondary nucleation and multilayer growth, and ensuring the monolayer nature and crystal integrity of the graphene film. In addition, continuous hydrogen introduction can maintain the hydrogen atmosphere in the furnace, preventing secondary oxidation of the copper surface during high-temperature growth and ensuring the stability of the graphene growth microenvironment.

[0068] For example, after the graphene growth is completed, the carbon source gas and hydrogen are turned off, and the graphene-copper composite material is cooled to room temperature by rapid or natural cooling under the protection of an inert gas (e.g., argon).

[0069] The present application will be specifically described below through specific embodiments. The following embodiments are only some embodiments of the present application and are not intended to limit the present application.

[0070] Example 1 A graphene-copper composite material, the preparation method of which includes: S1. Cleaning of the copper substrate, which is copper foil with an average thickness of 60μm and dimensions of 5cm × 2cm (length × width). The cleaning steps specifically include: S12. Cleaning of organic contaminants: Place the copper substrate in acetone, anhydrous ethanol and deionized water in sequence, and perform ultrasonic cleaning for 10 minutes each to remove oil, organic contaminants and some particulate impurities from the surface of the copper substrate. S13. Pickling: Immerse the copper substrate in a 2.59% hydrochloric acid solution for 75 seconds to thoroughly remove the uneven natural oxide layer; S14. Rinsing and drying: After pickling, rinse with plenty of deionized water, then ultrasonically rinse with deionized water for 5 minutes, and finally blow dry thoroughly with a high-purity nitrogen gun for later use.

[0071] S2. Uniform oxidation treatment with oxygen plasma, the specific steps of which include: S21. Equipment loading: Place the dried copper substrate into the reaction chamber of the plasma processing equipment; S22. Vacuuming and ventilation: Close the chamber, start the vacuum system, and evacuate the vacuum to below 40Pa. Then, introduce high-purity oxygen and stabilize the vacuum in the chamber at 80Pa by adjusting the slide valve or flow meter. Control the oxygen flow rate at 30sccm. S23. Plasma Treatment: Turn on the RF power supply, set the treatment power to 300W, and ignite oxygen plasma for 200 seconds. Under these parameters, the copper substrate surface reacts fully with the oxygen plasma, generating a uniform light brown oxide film (artificial oxide layer). After treatment, turn off the RF power supply, stop the gas supply, evacuate the chamber, and fill it with argon gas to ventilate the chamber before removing the sample.

[0072] S3. Graphene is grown by low-pressure CVD to prepare graphene-copper composite material. The specific steps include: S31. Loading the furnace: Place the copper substrate, which has been pre-oxidized by oxygen plasma, into the constant temperature zone of the CVD quartz tube reaction chamber; S32. Heating and Annealing: Close the furnace door and evacuate to the minimum vacuum of the CVD system (50 Pa). Begin heating under vacuum. When the temperature reaches 1030℃, introduce hydrogen gas at a flow rate of 250 sccm for high-temperature annealing at 1030℃ for 30 minutes. During this process, the hydrogen gas undergoes a reduction reaction with the uniform artificial oxide layer, achieving ultraplanar reconstruction of the copper substrate surface to obtain the copper substrate. S33. Graphene growth on copper substrate: After annealing, keep the temperature constant at 1020℃, and introduce 5 sccm of carbon source gas (methane) on the basis of hydrogen flow to grow graphene for 15 minutes. S34. Cooling: After growth, the carbon source gas and hydrogen gas are turned off, and the graphene copper composite material is cooled to room temperature by natural cooling under the protection of inert argon gas at 200 sccm.

[0073] Example 2 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is copper foil, and the average thickness of the copper foil substrate is 20 μm.

[0074] Example 3 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is copper foil, and the average thickness of the copper foil substrate is 100 μm.

[0075] Example 4 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper plate with an average thickness of 150 μm.

[0076] Example 5 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper plate with an average thickness of 1000 μm.

[0077] Example 6 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper block, which is rectangular in shape, with a length of 2cm, a width of 1cm, a height of 0.5cm, and a volume of 1cm³. 3 .

[0078] Example 7 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper block, which is rectangular in shape, with a length of 5cm, a width of 4cm, a height of 5cm, and a volume of 100cm³. 3 .

[0079] Example 8 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper strip with a diameter of 5mm.

[0080] Example 9 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper strip with a diameter of 15mm.

[0081] Example 10 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper matrix is ​​copper powder, and the average particle size of the copper powder is 15 μm.

[0082] Example 11 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper matrix is ​​copper powder, and the average particle size of the copper powder is 35 μm.

[0083] Example 12 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper matrix is ​​copper powder, and the average particle size of the copper powder is 50 μm.

[0084] Example 13 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper wire with a diameter of 0.05 mm.

[0085] Example 14 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper substrate is a copper wire with a diameter of 5mm.

[0086] Example 15 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper matrix is ​​copper foam, and the specific surface area of ​​the copper foam is 0.2 m². 2 / g.

[0087] Example 16 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S1, the copper matrix is ​​copper foam, and the specific surface area of ​​the copper foam is 0.8 m². 2 / g.

[0088] Example 17 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: S23. Plasma treatment: Turn on the radio frequency power supply, set the processing power to 400W, ignite to generate oxygen plasma, and the processing time is 150 seconds.

[0089] Example 18 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: S23. Plasma treatment: Turn on the radio frequency power supply, set the processing power to 150W, ignite to generate oxygen plasma, and the processing time is 400 seconds.

[0090] Example 19 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: S13. Pickling: Immerse the copper substrate in a 0.86% hydrochloric acid solution for 120 seconds.

[0091] Example 20 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: S13. Pickling: Immerse the copper substrate in a 4.31% hydrochloric acid solution for 30 seconds.

[0092] Example 21 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S32, the flow rate of hydrogen is 100 sccm.

[0093] Example 22 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S32, the flow rate of hydrogen is 400 sccm.

[0094] Example 23 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S32, when the temperature rises to 1000℃, hydrogen gas is introduced at a flow rate of 250 sccm for high-temperature annealing treatment at a temperature of 1000℃ for 40 minutes.

[0095] Example 24 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: In S32, when the temperature rises to 1060℃, hydrogen gas is introduced at a flow rate of 250 sccm for high-temperature annealing treatment at 1060℃ for 20 minutes.

[0096] Comparative Example 1 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: Step “S1. Routine cleaning of copper substrate” only includes “S11. Material preparation” and “S12. Cleaning of organic contaminants”, and does not include “S13. Pickling” and “S14. Rinsing and drying”. The operation steps of “S11. Material preparation” and “S12. Cleaning of organic contaminants” are the same as those in Example 1.

[0097] After step "S1. Conventional cleaning of copper substrate", step "S2. Uniform oxidation treatment with oxygen plasma" is omitted, and step "S3. Low-pressure CVD growth of graphene" is performed directly. The operation steps of step "S3. Low-pressure CVD growth of graphene" are the same as those in Example 1.

[0098] It can be seen that Comparative Example 1 did not use acid washing to remove the natural oxide layer on the surface of the copper substrate, nor did it perform oxygen plasma treatment on the surface of the copper substrate. Instead, it simply cleaned the copper substrate with the natural oxide layer and then directly grew graphene.

[0099] Comparative Example 2 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: After step "S1. Routine cleaning of copper substrate", step "S2. Uniform oxidation treatment with oxygen plasma" is omitted, and step "S3. Low-pressure CVD growth of graphene" is performed directly. The operation steps of step "S1. Routine cleaning of copper substrate" and step "S3. Low-pressure CVD growth of graphene" are the same as in Example 1.

[0100] As can be seen, Comparative Example 2 used acid pickling to remove the natural oxide layer on the surface of the copper substrate, but did not perform oxygen plasma treatment on the surface of the copper substrate, and directly grew graphene on the acid-pickled copper substrate.

[0101] Comparative Example 3 A graphene-copper composite material, the preparation method of which differs from that in Example 1, is as follows: Step “S1. Routine cleaning of copper substrate” only includes “S11. Material preparation” and “S12. Cleaning of organic contaminants”, and does not include “S13. Pickling” and “S14. Rinsing and drying”. The operation steps of “S11. Material preparation” and “S12. Cleaning of organic contaminants” are the same as those in Example 1.

[0102] After step "S1. Routine cleaning of the copper substrate", instead of step "S2. Uniform oxidation treatment with oxygen plasma", a step "electrochemical polishing" is set. The "electrochemical polishing" includes: placing the copper substrate in an electrolyte prepared by orthophosphoric acid, anhydrous ethanol and deionized water in a volume ratio of 700:300:100, using the cleaned copper substrate as the anode and a stainless steel plate of the same size as the cathode, and performing constant current polishing for 90 seconds at a current density of 30A / dm² under constant temperature of 25°C and magnetic stirring; immediately after polishing, the substrate is removed and cleaned and dehydrated in sequence with deionized water, dilute phosphoric acid and ethanol.

[0103] After “electrochemical polishing”, step “S3. Low-pressure CVD growth of graphene” is performed directly, and the operation steps of step “S3. Low-pressure CVD growth of graphene” are the same as those in Example 1.

[0104] Performance testing: The copper matrix and the prepared graphene-copper composite material in the examples and comparative examples were subjected to performance tests. The test indicators and test methods are as follows: (1) Oxygen content of copper substrate: The oxygen content of the copper substrate (copper foil) was tested by melting-infrared absorption method using an oxygen-nitrogen-hydrogen analyzer (ONH Analyzer).

[0105] (2) Cu / O atomic ratio on copper substrate surface: The Cu / O atomic ratio on the copper substrate (copper foil) surface was measured by X-ray photoelectron spectroscopy (XPS). High-resolution spectra of Cu 2p and O 1s were collected, and the atomic ratio of Cu to O was calculated by the relative sensitivity factor method, thus obtaining the surface Cu / O atomic ratio.

[0106] (3) Oxide layer uniformity: The uniformity of the oxide layer was evaluated using XPS surface mapping. Within a 10 μm × 10 μm scanning area, O 1s or Cu 2p spectra were collected from at least 9 feature points. The relative standard deviation (RSD) of the oxide layer thickness was calculated based on the spectra of each point. The uniformity criteria were as follows: RSD > 15% was defined as "uneven depth, island-like distribution"; RSD < 10% was defined as "uniform depth, continuous and dense".

[0107] (4) Surface roughness RMS of graphene-copper composites: Characterization was performed using atomic force microscopy (AFM) in tapping mode. The scanning range was 1 μm × 1 μm, the scanning rate was 1.0 Hz, and the resolution was 512 × 512 pixels. The probe was an RTESP or a similar Si probe with an elastic constant of approximately 40 N / m and a resonance frequency of approximately 300 kHz. For graphene-copper composites with copper foil, copper plate, copper foam, copper wire, copper strip, and copper block as the copper matrix, the surface RMS roughness could be obtained directly by AFM testing. For graphene-copper composites with copper powder as the copper matrix, due to the strong particle dispersion and difficulty in fixation, a pressing treatment (pressure 1.0–1.5 MPa, holding pressure for 60 s) was required to aggregate the copper powder particles and form a stable test surface. This treatment condition ensured sufficient mechanical stability of the sample while avoiding excessive compaction deformation that could alter the surface morphology of the copper powder, thereby reducing the impact on the AFM surface roughness (RMS) test results.

[0108] (5) Oxygen element increment per unit surface area of ​​graphene-copper composite material: Characterization was performed using the oxygen content increment method. Graphene-copper composite materials prepared in the examples and comparative examples were cut into appropriately sized samples, and the initial oxygen element mass of each sample was measured. The samples were placed in air naturally for 14 days, and the oxygen element mass of the samples after 14 days was measured. The oxygen element increment per unit surface area of ​​samples with different morphologies was calculated. The surface area of ​​the samples was determined as follows: for copper foil, copper plate, copper strip, and copper block, the geometric dimensions were measured using vernier calipers, and the geometric surface area was calculated; for copper wire, the lateral area was calculated as length × cross-sectional perimeter; for copper powder and foamed copper, the specific surface area was determined using the BET nitrogen adsorption method, and then multiplied by the mass to obtain the total surface area. The smaller the value, the better the oxidation resistance of the graphene-copper composite material in the environmental atmosphere.

[0109] The test objects (copper substrates) for the three performance parameters "oxygen content of copper substrate", "Cu / O atomic ratio of copper substrate surface" and "uniformity of oxide layer" include: copper substrates after step "S2. oxygen plasma uniform oxidation treatment" in Examples 1 to 3 (with artificial oxide layer on the surface), copper substrates after step "S1. conventional cleaning of copper foil" in Comparative Example 1 (with natural oxide layer on the surface), copper substrates after step "S1. conventional cleaning of copper foil" in Comparative Example 2 (with natural oxide layer removed by acid pickling), and copper substrates after "electrochemical polishing" in Comparative Example 3 (with natural oxide layer removed by electrochemical polishing and extremely thin passivation layer formed).

[0110] The test object for the performance parameter "Surface Roughness RMS of Graphene Copper Composite Material" is the final product obtained by the examples and comparative examples - graphene copper composite material (including copper matrix and graphene film attached to the surface of copper matrix).

[0111] The test results are shown in Table 1.

[0112] Table 1

[0113] As can be seen from Table 1: (1) After oxygen plasma treatment, the copper substrates of Examples 1-24 have a uniform and continuously distributed artificial oxide film on their surface, which provides a structural basis for the synchronous reduction and surface superplanarization reconstruction in the subsequent hydrogen annealing.

[0114] (2) Although the copper substrate in Comparative Example 2 has no stable oxide layer after pickling, a very small amount of surface oxygen signal can still be detected. This signal may come from residual adsorbed oxygen on the surface or a very thin natural oxide layer.

[0115] (3) The surface roughness of the graphene copper composite materials prepared in Examples 1-24 is extremely low (3nm~45nm), while the surface roughness of the graphene copper composite material prepared in Comparative Example 1 is as high as 116nm; the surface roughness of the graphene copper composite material prepared in Comparative Example 2 is 92nm, and the surface roughness of the graphene copper composite material prepared in Comparative Example 3 is 58nm. By comparison, it can be seen that the surface roughness of the graphene copper composite materials prepared in Examples 1-24 is much lower than that of Comparative Examples 1-3, indicating that the surface of the graphene copper composite materials prepared in Examples 1-24 is relatively smooth. The graphene film is laid flat on the copper substrate, and the two are closely bonded, which can effectively reduce the interfacial gap between the graphene film and the copper substrate.

[0116] (4) In the antioxidant performance test, the increase in oxygen element per unit surface area of ​​the graphene copper composite material in Examples 1-24 was significantly lower than that in Comparative Examples 1-3, indicating that the graphene copper composite material prepared in Examples 1-24 has better antioxidant performance.

[0117] Graphene performance testing: (1) Size L of single-crystal graphene: The single-crystal graphene was characterized by scanning electron microscopy (SEM). At least 5 fields of view were randomly selected to directly observe the morphology of graphene domains on the copper substrate. The longest diagonal or equivalent diagonal of each domain was measured (for regular domains such as hexagons, the longest diagonal was directly measured; for irregular domains, the longest diagonal of the equivalent area regular hexagon was measured as the equivalent diagonal). The maximum value of the domain size in all fields of view was taken as the size L of single-crystal graphene.

[0118] (2) Monolayer ratio: Characterization was performed using a 532 nm Raman spectrometer. 100 test points were randomly selected within a 0.5 cm × 0.5 cm sample area, and Raman spectra were collected at each point. The criteria for determining monolayer graphene were: the 2D peak exhibited a single Lorentz symmetric peak shape, and the intensity ratio of the 2D peak to the G peak (Ig) was [missing information]. 2D / I G ≥2. The single-layer rate is calculated according to the following formula: Single-layer rate = (Number of test points meeting the single-layer standard / Total number of test points) × 100%.

[0119] (3) 2D / G intensity ratio: Characterization was performed using a 532nm Raman spectrometer. 100 test points were randomly selected within a 0.5cm × 0.5cm sample area. Each test point was located inside the graphene domains, avoiding the domain edges. Raman spectra of each point were collected, and the 2D peak (approximately 2700cm) of each test point was read. -1 ) and G peak (approximately 1580cm) -1 The peak intensity of ) is calculated, and the peak intensity ratio (I) is calculated. 2D / I G The average value of the results from 100 test points was taken as the 2D / G intensity ratio, and the standard deviation was calculated.

[0120] (4) D / G intensity ratio: Characterization was performed using a 532 nm wavelength Raman spectrometer. 100 test points were randomly selected within a 0.5 cm × 0.5 cm sample area, with each test point located within the graphene domains, avoiding the domain edges. Raman spectra were collected at each point, and the D peak (approximately 1350 cm⁻¹) was read from each test point. -1 ) and G peak (approximately 1580cm) -1 The peak intensity of ) is calculated, and the peak intensity ratio (I) is calculated. D / I GThe average value of 100 test points was taken as the D / G intensity ratio, and the standard deviation was calculated. The D / G intensity ratio reflects the defect density of graphene; the lower the ratio, the fewer the lattice defects. It is generally believed that I... D / I G <0.05 indicates high-quality graphene, I D / I G A value greater than 0.2 indicates a high number of defects.

[0121] The test results are shown in Table 2.

[0122] Table 2

[0123] As can be seen from Table 2: (1) The single-crystal graphene size L of the graphene films prepared in Examples 1-24 is larger than that in Comparative Examples 1-3, indicating that after constructing a uniform artificial oxide layer by oxygen plasma pretreatment and achieving superplanarization of the copper substrate surface by hydrogen annealing, the nucleation density of graphene is effectively suppressed, and a single crystal nucleus obtains sufficient lateral growth space, thereby realizing the growth of large single-crystal graphene.

[0124] (2) The monolayer ratio and 2D / G intensity ratio of the graphene films prepared in Examples 1-24 are higher than those in Comparative Examples 1-3, indicating that the graphene films grown on the ultraplanarized copper substrate surface in this application have higher monolayer uniformity. This is because the ultraplanarized surface eliminates the rough defects and additional nucleation sites that induce multilayer growth, allowing the self-limited growth mechanism of copper-based CVD (chemical vapor deposition) to play a full role on the ideal surface.

[0125] (3) The D / G strength ratio of the graphene films prepared in Examples 1-24 is lower than that of Comparative Examples 1-3, indicating that the graphene prepared in Examples 1-24 has extremely high crystal integrity and extremely low defect density. This is because the ultra-flat copper substrate significantly reduces the number of graphene grain boundaries, and the low nucleation density avoids the collision and merging of grains, thereby ensuring the excellent crystal quality of the graphene film.

[0126] The above results indicate that by treating the copper substrate with oxygen plasma, this application actively constructs an artificial oxide layer with uniform and controllable thickness and chemical composition on the surface of the copper substrate. This artificial oxide layer undergoes a synchronous and uniform reduction reaction during subsequent hydrogen annealing, driving long-range surface migration and rearrangement of copper atoms, ultimately resulting in a copper substrate with an ultra-flat surface. The graphene film grown on this copper substrate exhibits excellent comprehensive properties, including large single crystal size, high monolayer ratio, high 2D / G intensity ratio, and low D / G intensity ratio.

[0127] The graphene-copper composite material and its preparation method provided in the embodiments of this application have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the embodiments above are only for the purpose of helping to understand this application. Furthermore, those skilled in the art will recognize that, based on the ideas of this application, there will be changes in the specific implementation methods and application scope. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A graphene-copper composite material, characterized in that, The invention includes a copper substrate and a graphene film attached to the surface of the copper substrate, wherein the ratio L / RMS of the size of the single-crystal graphene in the graphene film to the surface roughness RMS of the graphene-copper composite material satisfies: 444≤L / RMS≤11000.

2. The graphene-copper composite material according to claim 1, characterized in that, The macroscopic physical morphology of the copper substrate is selected from at least one of copper foil, copper plate, copper strip, copper block, copper powder, copper foam, and copper wire; The average thickness of the copper foil is 20μm~100μm; The average thickness of the copper plate is 100μm~1000μm; The equivalent circle diameter of the cross-section of the copper strip is 5mm to 15mm; The volume of the copper block is 1 cm³. 3 ~100cm 3 ; The average particle size of the copper powder is 15μm~50μm; The specific surface area of ​​the copper foam is 0.2 m². 2 / g~0.8m 2 / g; The equivalent circle diameter of the cross-section of the copper wire is 0.05mm to 5mm.

3. The graphene-copper composite material according to claim 2, characterized in that, The macroscopic physical morphology of the copper substrate is selected from at least one of copper foil, copper plate, copper strip, and copper block; the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene copper composite material satisfies: 800≤L / RMS≤11000. The single-crystal graphene size L in the graphene film satisfies: 24μm≤L≤55μm; the surface roughness RMS of the graphene-copper composite material satisfies: 5nm≤RMS≤30nm.

4. The graphene-copper composite material according to claim 3, characterized in that, The graphene film has a monolayer ratio of 90%~98%; and / or, The graphene film has a 2D / G strength ratio of 1.9 to 4.6; and / or, The D / G intensity ratio of the graphene film is 0.03~0.

09.

5. The graphene-copper composite material according to claim 2, characterized in that, The macroscopic physical morphology of the copper matrix is ​​selected from at least one of copper powder, copper foam, and copper wire; the ratio L / RMS of the single-crystal graphene size L in the graphene film to the surface roughness RMS of the graphene copper composite material satisfies: 444≤L / RMS≤2000. The single-crystal graphene size L in the graphene film satisfies: 20μm≤L≤32μm; the surface roughness RMS of the graphene-copper composite material satisfies: 16nm≤RMS≤45nm.

6. The graphene-copper composite material according to claim 5, characterized in that, The monolayer ratio of the graphene film is 82%~92%; and / or, The graphene film has a 2D / G intensity ratio of 1.7 to 3.4; and / or, The graphene film has a D / G intensity ratio of 0.05 to 0.

13.

7. A method for preparing a graphene-copper composite material, characterized in that, include: Provide a copper substrate and remove the natural oxide layer on the surface of the copper substrate; The copper substrate is subjected to oxygen plasma treatment to generate an artificial oxide layer on the surface of the copper substrate; The copper substrate is annealed in a hydrogen atmosphere to remove the artificial oxide layer; A graphene film is grown on the surface of the copper substrate to obtain a graphene-copper composite material.

8. The method for preparing the graphene-copper composite material according to claim 7, characterized in that, The removal of the natural oxide layer on the surface of the copper substrate includes immersing the copper substrate in a hydrochloric acid solution for 30 to 120 seconds, wherein the mass percentage of hydrochloric acid in the hydrochloric acid solution is 0.86 wt% to 4.31 wt%.

9. The method for preparing the graphene-copper composite material according to claim 7, characterized in that, The oxygen plasma treatment of the copper substrate includes: The copper substrate is placed in the reaction chamber of the plasma processing equipment, and oxygen is introduced into the reaction chamber at a flow rate of 3 sccm to 50 sccm. The radio frequency power supply of the plasma processing equipment is turned on, with an output power of 150W to 400W and a processing time of 150 seconds to 400 seconds.

10. The method for preparing the graphene-copper composite material according to claim 7, characterized in that, The annealing treatment of the copper substrate in a hydrogen atmosphere includes: In a vacuum environment, or with an inert gas introduced, the copper substrate is heated to 1000°C to 1060°C. Hydrogen gas is introduced to form a hydrogen atmosphere, and the copper substrate is kept at 1000℃~1060℃ for 20 minutes to 40 minutes in the hydrogen atmosphere.

11. The method for preparing the graphene-copper composite material according to claim 10, characterized in that, The flow rate of the hydrogen gas is 100 sccm to 400 sccm.

12. The method for preparing the graphene-copper composite material according to any one of claims 7-11, characterized in that, After an artificial oxide layer is formed on the surface of the copper substrate, the oxygen content of the copper substrate having the artificial oxide layer is 60ppm to 650ppm; and / or, the Cu / O atomic ratio of the artificial oxide layer is 1 to 4.